A strategy developed from the observed energetic–energetic cocrystals of BTF: cocrystallizing and stabilizing energetic hydrogen-free molecules with hydrogenous energetic coformer molecules1. Issue 37 (7th October 2015) - Wei, Xianfeng; Ma, Yu; Long, Xinping; Zhang, Chaoyang
<x xml:space="preserve">Abstract</x> We propose a strategy to combine highly energetic but unstable hydrogen-free molecules with hydrogenous energetic molecules to form stable energetic–energetic cocrystals and maintain their high energy, developed by analyzing the crystal packing of BTF-based EECCs.